(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
Mining is a high-risk industry that exposes operators and workers to a high level of occupational health and safety hazards caused by vehicle accidents, blasting, or collapse. This paper aims to analyse the serious and fatal accidents in Iran’s mines over a six-year period, from 2012 to 2017. The data sources were the statistical results of the occupational accidents reported by the National Statistical Centre of Iran and the importance measure of incidents defined by the questionnaires received from the mine safety and health experts. This research presents a model for the prioritization of the mining workplace based on the weighted injury risk of the occupational incidents in the mining industry. The results of this work show that the coal mines of Iran have the highest work-related incidence rate which requires special safety attention. Moreover, the total temporary disability risk is currently at the lowest level in all mining activities, while the fatality risk has significantly increased in the coal mines in recent years. The results obtained from this study are helpful to detect the dangerous mining workplaces and to protect workers from workplace hazards by considering the safety guidelines.